Anti-inflammatory effects of the new generation synthetic surfactant CHF5633 on Ureaplasma-induced cytokine responses in human monocytes. Issue 2 (1st February 2017) - Glaser, Kirsten; Fehrholz, Markus; Henrich, Birgit; Claus, Heike; Papsdorf, Michael; Speer, Christian P.
ABSTRACT: Background: Synthetic surfactants represent a promising alternative to animal-derived preparations in the treatment of neonatal respiratory distress syndrome. The synthetic surfactant CHF5633 has proven biophysical effectiveness and, moreover, demonstrated anti-inflammatory effects in LPS-stimulated monocytes. With ureaplasmas being relevant pathogens in preterm lung inflammation, the present study addressed immunomodulatory features on Ureaplasma -induced monocyte cytokine responses. Methods: Ureaplasma parvum -stimulated monocytes were exposed to CHF5633. TNF-α, IL-1β, IL-8, IL-10, TLR2 and TLR4 expression were analyzed using qPCR and flow cytometry. Results: CHF5633 did not induce pro-inflammation, and did not aggravate Ureaplasma -induced pro-inflammatory cytokine responses. It suppressed U. parvum -induced intracellular TNF-α (p < 0.05) and IL-1β (p < 0.05) in neonatal monocytes and inhibited Ureaplasma -induced TNF-α mRNA (p < 0.05), TNF-α protein (p < 0.001), and IL-1β (p = 0.05) in adult monocytes. Ureaplasma -modulated IL-8, IL-10, TLR2 and TLR4 were unaffected. Conclusion: CHF5633 does neither act pro-apoptotic nor pro-inflammatory in native and Ureaplasma -infected monocytes. Suppression of Ureaplasma -induced TNF-α and IL-1β underlines anti-inflammatory features of CHF5633.